PUBLIC PARTICIPATION AS A BASIS FOR PUBLIC TRUST IN PUBLIC ADMINISTRATION: PROBLEMS AND CHALLENGES IN LATVIA - Mirlina, Liga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Nowadays, many public administrations are facing the low level of public trust in state authorities. It is largely due to public dissatisfaction with the activities of public administration and beliefs that public administration does not serve to the public interest. Participation in decision-making processes is one of the ways to reduce public dissatisfaction and mistrust in public administration. In order to understand the importance of public participation in public administration processes, the aim of the paper is to study trends in the transformation of public administration and society at different stages of the development of the state reform in Latvia and its impact on public trust in public administration. The following methods have been used in the research study: analysis of normative documents, an expert survey with non-governmental organizations (NGOs) and government representatives, as well as analysis of statistics on the implementation of the Memorandum of Cooperation between the government and NGOs. An analysis of the normative documents adopted by the Latvian government shows that the legal framework provides for wide opportunities for NGO involvement in public administration. The statistical data and opinions of NGOs and public administration experts show that there are a variety of mechanisms for increasing NGOs participation. However, the opportunities for developed participation are not conducive to public trust in the public administration, since in most cases information about the opportunities and results of participation is not reachable to the general public. Thus, it is vitally important to create an optimal model of NGOs and public administration relations for the activation of Latvian society in order to reduce the low participation and public trust in public administration.